Discourse analysis in sequence novels by Leila S. Chudori (2012, 2017) - Widyaiswara, Tiara; Setyaningrum, Riya Risqi; Affandy, Ali Nuke (Politeknik Negeri Bali, 2022)
This research is about the resistance of life characters from political exiles and student activists in 1998 contained in the novels Pulang and Laut Bercerita by Chudori (2012, 2017). The focus of this study is the Foucault (2012) discourse analysis which focuses on resistance characters in fighting the New Order regime. This study aims to examine the patterns of resistance through discursive formations in archeological reading. The steps of analysis are; to mark it based on existing discourse, link the lines of text with the sequence, observed the rupture, interpretation of the meaning. The results of the study show that Chudori's novels have patterns of resistance that cannot be separated from the New Order regime that once ruled Indonesia. This is based on the discursive formation that occurs in the text that describes if the power of the New Order regime is very strong.